2021
DOI: 10.1101/2021.04.07.438845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enabling constrained spherical deconvolution and diffusional variance decomposition with tensor-valued diffusion MRI

Abstract: Diffusion tensor imaging (DTI) is widely used to extract valuable tissue measurements and white matter (WM) fiber orientations, even though its lack of specificity is now well-known, especially for WM fiber crossings. Models such as constrained spherical deconvolution (CSD) take advantage of HARDI data to compute fiber orientation distribution functions (fODF) and tackle the orientational part of the DTI limitations. Furthermore, the recent introduction of tensor-valued diffusion MRI allows for diffusional var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…However, SS3T-CSD signal fraction maps have not been confronted with ACT. Jeurissen and Szczepankiewicz ( 2021 ) and Karan et al ( 2021 ) recently showed that having a tensor-value DWI using linear and spherical encoding helps WM, GM, and CSF signal fraction estimation. This method requires a very specific multi-dimensional b-tensor encoding acquisition scheme and is not easily applicable to actual well-known databases such as HCP, ADNI, and UKBiobank.…”
Section: Discussionmentioning
confidence: 99%
“…However, SS3T-CSD signal fraction maps have not been confronted with ACT. Jeurissen and Szczepankiewicz ( 2021 ) and Karan et al ( 2021 ) recently showed that having a tensor-value DWI using linear and spherical encoding helps WM, GM, and CSF signal fraction estimation. This method requires a very specific multi-dimensional b-tensor encoding acquisition scheme and is not easily applicable to actual well-known databases such as HCP, ADNI, and UKBiobank.…”
Section: Discussionmentioning
confidence: 99%